2012
DOI: 10.11606/issn.2316-9060.v8i0p125-137
|View full text |Cite
|
Sign up to set email alerts
|

Atendimento a Criatórios de Bovinos e Pequenos Ruminantes Localizados na Grande São Paulo

Abstract: FMVZ) se baseiam nos três pilares fundamentais da Universidade de São Paulo: ensino, pesquisa e extensão. O presente projeto teve o objetivo de propiciar a estudantes de medicina veterinária o aprendizado e treinamento prático das principais técnicas de diagnóstico e tratamento das enfermidades que acometem os ruminantes, auxiliando o atendimento do hospital e atendendo aos anseios da comunidade. Com a Clínica Ambulante, foi possível o atendimento a propriedades perto de São Paulo, com cuidados veterinários ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
(5 reference statements)
0
2
1
3
Order By: Relevance
“…In order to establish the occurrence of the main diseases that affect cattle, highlighting the different organic systems, other studies based on clinical cases, showed variation in the frequency of diseases that affect the digestive system of cattle, in different regions of Brazil. However, the number of animals studied, as well as the observation time, were lower than the present study (Tortorelli et al 2012, Borowsky et al 2019, Oliveira et al 2019.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In order to establish the occurrence of the main diseases that affect cattle, highlighting the different organic systems, other studies based on clinical cases, showed variation in the frequency of diseases that affect the digestive system of cattle, in different regions of Brazil. However, the number of animals studied, as well as the observation time, were lower than the present study (Tortorelli et al 2012, Borowsky et al 2019, Oliveira et al 2019.…”
Section: Discussioncontrasting
confidence: 69%
“…These studies demonstrated regional variation in the occurrence of diseases affecting the digestive system of cattle, and often classify them by etiology into nutricional and metabolic diseases. These diseases were responsible for approximately 10% of the clinical cases of ruminants attended at the Veterinary Teaching Hospital of the "Universidade Federal do Rio Grande do Sul" (UFRGS; 6/60) (Borowsky et al 2019), as well as at the Bovine and Small Ruminant Hospital of the "Faculdade de Medicina Veterinária e Zootecnia", "Universidade de São Paulo" (USP; 9/88) (Tortorelli et al 2012) and 21% (74/351) of the clinical cases of admitted treated at the Veterinary Hospital of the "Escola deMedicina Veterinária e Zootecnia" at the "Universidade Federal do Tocantins" (Oliveira et al 2019). In the State of Pernambuco, Afonso (2017) reported that diseases of the bovine digestive system represent approximately 18% of the cases at the "Clínica de Bovinos de Garanhuns", "Universidade Federal Rural de Pernambuco" (CBG-UFRPE).…”
Section: Introductionmentioning
confidence: 99%
“…A miíase representou 42,85% dos casos em ovinos, 20% em caprinos e 16,66% dos casos em bovinos. Em estudo prévio realizado em São Paulo, a miíase não teve grande casuística no atendimento de ruminantes [32].…”
Section: Materiais E Métodosunclassified
“…A verminose representou 25,71% dos casos diagnosticados em ovinos, 37,5% em caprinos e 11,11% dos atendimentos em bovinos. Estudos prévios colocam a verminose como principal doença infectocontagiosa em pequenos ruminantes [2,10,27,29,32].…”
Section: Materiais E Métodosunclassified
See 1 more Smart Citation